Ethnic Identity as a Factor in Preservation and Development of Ukrainian Ethnocultural Singularity - Olha Shakurova (Українознавство, 2020)
The article analyzes the influence of ethnic identity on the preservation and development of ethnocultural singularity. It is determined that the preservation of an ethnos’ singularity is possible only if the majority of its members have a stable and positive ethnic identity. It is noted that the ethnic community, whose members feel a strong and continuous relation to the moral and spiritual heritage of their ancestors, has a powerful internal potential for further development and preservation of its ethnocultural identity and uniqueness. It is shown that the ethnic identity constitutes a key concept for a number of humanities and has a complex structure that includes three main components – cognitive, affective, and behavioral one. The article characterizes linguocognitive parameters of the ethnic identity. It highlights the existence of positive and negative identities and emphasizes that a stable and positive ethnic identity provides a sense of group security and stability, because the more members of an ethnic group share a common ethnic identity, the greater is the likelihood of their joint action to protect political interests. The research considers factors that contribute to the preservation of ethnocultural identity and factors that cause its loss or transformation. It is determined that building a stable and positive Ukrainian identity requires purposeful and thoughtful steps on the part of the state, namely promotion of customs and traditions of the Ukrainian people, their material and spiritual culture; informing about the achievements of their prominent representatives and active formation of national prestige. It has been shown that for modern man, ethnic identity becomes an important foundation and support, because it symbolizes a continuous connection with the traditions and values of the past, the stages of ethnic stability. It is emphasized that only by understanding one’s belonging to a certain ethnic group, mastering cultural norms and traditions, a person can effectively immerse themselves in social processes and feel like a full member of the society.